"Translators are bridge builders, linking people and cultures": An interview with Mohammad A. Quayum. Issue 2 (3rd July 2022) - Islam, Mohammad Shafiqul
ABSTRACT: This interview conducted with Mohammad A. Quayum from October 2021 to February 2022 focuses on a wide range of issues in literary translation and Translation Studies. Quayum is one of the leading academics and translators from Bangladesh, currently teaching at Flinders University, Australia.A renowned professor of English literature teaching in various countries, including Australia, Bangladesh, Malaysia, Singapore, and the US, Quayum has published numerous books and scholarly articles in renowned journals. His works have also drawn critical attention as they have been published by Brill, Penguin Books, Routledge, Springer and Stanford University Press. Quayum has already translated and published major writers and poets of Bengali literature into English, including Rabindranath Tagore (1861–1941), Rokeya Sakhawat Hossain (1880–1932) and Kazi Nazrul Islam (1899–1976). In this interview, Quayum offers valuable insights about literary translation and his translated works. He argues that translation, which is an inter-lingual as well as inter-cultural activity, builds bridges between cultures. In his view, translators require clarity of mind and lots of free-floating energy to keep focused on their work. The interview touches upon Quayum's deep involvement in research and translation activities, his thoughts on literary translation and Translation Studies, and the current state and prospects of literary translation in Bangladesh.